Small mammals (Didelphimorphia, Rodentia and Chiroptera) from Pampean Region, Argentina - Fernández, Fernando Julián (2012)
We studied small mammal assemblages recovered from owl pellets collected at 11 locations throughout the Argentina's Pampean Region. We identified 21 species, including two marsupials, one bat, and 18 rodents. From the analysis of this dataset, we could distinguish three main groups of small mammals that currently inhabit the Pampean Region: 1) a group of taxa related to Pampean agroecosystems (Calomys spp., Akodon azarae, and Oligoryzomys flavescens); 2) a group of Brazilian species (Cavia aperea, Oxymycterus rufus, Necromys lasiurus, Necromys obscurus, Holochilus brasiliensis, and Monodelphis dimidiata); and 3) a group including species from Patagonia, Espinal and Monte phytogeographic provinces (Microcavia australis, Oligoryzomys longicaudatus, Eligmodontia typus, Graomys griseoflavus, and Akodon molinae). In addition, we documented the first record of a species of the large-bodied group of Calomys in Buenos Aires province, expanding its distribution ca. 420 km southward.